Hired to be fired? Being a coach in Danish professional football - Nissen, R. (International Journal of Sports Science & Coaching, 2016)
From a European perspective, the number of coach dismissals in professional football seems to be increasing. However, besides this apparent `hire and fire` mentality in football, few studies have aimed at examining what being a football coach entails. By combining Norbert Elias`s game models and the concept of trust in organisations, this study shows how today`s coach functions in a complex figuration and is engaged in multiple interdependencies. In times of sporting failure, this figuration tends to become more complex, as the coach is typically put under pressure internally and externally. By focusing on the relationship between a coach and his director and on how this relationship changes when performance is low, this study contributes with new insights into what it involves to be a top coach and at the same time offers potential explanations for why the frequency of dismissals seems to be increasing.